Clinical and financial impacts of abnormal liver biochemistry after liver transplantation - Dee Zhen Lim; Nicholas Low; Louise Jackett; Ronald Ma; Robert Jones; Adam Testro; Laurence Weinberg; Muralidharan Vijayaragavan (BMC Research Notes, 2023)
Abstract Objective After liver transplant (LT), many investigations are needed to evaluate abnormal liver function test (LFT), which has poor specificity for graft function and complication. A single center retrospective audit of all adult single organ LT from 1/1/2015 to 31/12/2017 was performed. Demographic, clinical and investigation data from the LT database and electronic medical records and cost data from the hospital’s Business Intelligence Unit were analyzed. Patients were classified into uncomplicated or complicated LFT by 2 independent investigators and the number, type, and cost of investigations in the first 30 post-operative days were analyzed. Investigations prior to liver biopsy was sub-analyzed. Results There was 170 LT with 87 cases of uncomplicated LFT (51.2%) and 83 cases of complicated LFT (48.8%). Most patients with complicated LFT had additional investigations (97.6%), most commonly cholangiogram (55.4%) and liver biopsy (LBx) (50.6%). The additional investigations cost was $1863.3 (95% CI 1289.0–2437.6). Although most LBx (73.8%) showed evidence of rejection, LBx was often not the initial investigation of choice. Current LFT based post-transplant monitoring is inefficient. It remains difficult to determine which patient will benefit from an early invasive procedure like LBx, using LFT alone without further imaging investigations.